2011
DOI: 10.1186/1471-2407-11-81
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of promoter methylation in the regulation of Pregnane X receptor in colon cancer cells

Abstract: BackgroundPregnane X receptor (PXR) is a key transcription factor that regulates drug metabolizing enzymes such as cytochrome P450 (CYP) 3A4, and plays important roles in intestinal first-pass metabolism. Although there is a large inter-individual heterogeneity with intestinal CYP3A4 expression and activity, the mechanism driving these differences is not sufficiently explained by genetic variability of PXR or CYP3A4. We examined whether epigenetic mechanisms are involved in the regulation of PXR/CYP3A4 pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 25 publications
1
54
0
1
Order By: Relevance
“…Our data are consistent with previous observations that PXR is antiapoptotic in colon (e.g., upregulates antiapoptotic BAG3, BIRC2, and MCL-1, while downregulating proapoptotic BAK1 and p53) (15,54) and ovarian cancer (20,55) and generally support the notion that PXR is associated with protection from xenobiotic damage (e.g., cellular drug resistance) (54,(56)(57)(58)(59). However our observations are in stark contrast to recent observations that PXR induces apoptosis in colon (60) and breast cancer (18) and predicts for significantly improved survival in esophageal cancer (61).…”
Section: Discussionsupporting
confidence: 82%
“…Our data are consistent with previous observations that PXR is antiapoptotic in colon (e.g., upregulates antiapoptotic BAG3, BIRC2, and MCL-1, while downregulating proapoptotic BAK1 and p53) (15,54) and ovarian cancer (20,55) and generally support the notion that PXR is associated with protection from xenobiotic damage (e.g., cellular drug resistance) (54,(56)(57)(58)(59). However our observations are in stark contrast to recent observations that PXR induces apoptosis in colon (60) and breast cancer (18) and predicts for significantly improved survival in esophageal cancer (61).…”
Section: Discussionsupporting
confidence: 82%
“…42 PXR plays an important role in the regulation of CYP3A4, a major DME in humans. 43 In a previous study, swimming exercise for 8 weeks was found to increase mRNA and protein expression of PPAR in elderly mice, and the expression of 3-hydroxyacyl CoA dehydrogenase and carnitine palmitoyl transferase-I, target genes of PPAR, was also increased in the heart. 44 Thus, our findings support that exercise may prevent the increased drug toxicity observed in elderly individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of PXR through the hypermethylation of its CpG-rich promoter regions is associated with aggressive neuroblastoma (Misawa et al 2005), while a decrease in methylation of PXR promoter is correlated with colorectal cancer (Habano et al 2011). The restoration of PXR expression in neuroblastoma cells results in growth suppression of the cells, suggesting a tumor suppressive property of PXR (Misawa et al 2005).…”
Section: Regulation Of Pregnane X Receptor and Its Target Genesmentioning
confidence: 99%